Non-compliance with colonoscopy after a positive faecal immunochemical test doubles the risk of dying from colorectal cancer. Issue 3 (31st March 2021) - Zorzi, Manuel; Battagello, Jessica; Selby, Kevin; Capodaglio, Giulia; Baracco, Susanna; Rizzato, Silvia; Chinellato, Enrico; Guzzinati, Stefano; Rugge, Massimo
Abstract : Background: The risk of colorectal cancer (CRC) among subjects with a positive faecal immunochemical test (FIT) who do not undergo a colonoscopy is unknown. We estimated whether non-compliance with colonoscopy after a positive FIT is associated with increased CRC incidence and mortality. Methods: The FIT-based CRC screening programme in the Veneto region (Italy) invited persons aged 50 to 69 years with a positive FIT (>20 µg Hb/g faeces) for diagnostic colonoscopy at an endoscopic referral centre. In this retrospective cohort study, we compared the 10-year cumulative CRC incidence and mortality among FIT positives who completed a diagnostic colonoscopy within the programme (compliers) and those who did not (non-compliers), using the Kaplan-Meier estimator and Cox-Aalen models. Results: Some 88 013 patients who were FIT positive complied with colonoscopy (males: 56.1%; aged 50–59 years: 49.1%) while 23 410 did not (males: 54.6%; aged 50–59 years: 44.9%). The 10-year cumulative incidence of CRC was 44.7 per 1000 (95% CI, 43.1 to 46.3) among colonoscopy compliers and 54.3 per 1000 (95% CI, 49.9 to 58.7) in non-compliers, while the cumulative mortality for CRC was 6.8 per 1000 (95% CI, 5.9 to 7.6) and 16.0 per 1000 (95% CI, 13.1 to 18.9), respectively. The risk of dying of CRC among non-compliers was 103% higher than among compliers (adjusted HR, 2.03; 95% CI, 1.68 to 2.44). Conclusion: The excess risk of CRC death among those not completing colonoscopy after a positive faecal occult blood test should prompt screening programmes to adopt effective interventions to increase compliance in this high-risk population.